I.G.Y. Ascaplots : half-hourly auroral all-sky camera plots from 115 stations for the period 1958-1959 - Stoffregen, W. (Annals of the International Geophysical Year, 1963)
Annals of the International Geophysical Year, Volume 20, Part II: I.G.Y. Ascaplots is a four-chapter text that provides the data on half-hourly auroral all-sky camera plots from 115 stations for the period 1958-1959. This period cover two winters in the northern hemisphere characterized by high auroral activity. This part also presents the list of stations, as well as the maps of the northern and southern distribution of all-sky cameras, with some modifications and additions to the earlier list. Data from the added Japanese station in the Antarctic are received and are included with the data.